Phakomatoses and Endocrine Gland Tumors: Noteworthy and (Not so) Rare Associations - Chevalier, Benjamin; Dupuis, Hippolyte; Jannin, Arnaud; Lemaitre, Madleen; Do Cao, Christine; Cardot-Bauters, Catherine; Espiard, Stéphanie; Vantyghem, Marie Christine (Frontiers in Endocrinology, 2021)
Phakomatoses encompass a group of rare genetic diseases, such as von Hippel-Lindau syndrome (VHL), neurofibromatosis type 1 (NF1), tuberous sclerosis complex (TSC) and Cowden syndrome (CS). These disorders are due to molecular abnormalities on the RAS-PI3K-Akt-mTOR pathway for NF1, TSC and CS, and to hypoxia sensing for VHL. Phakomatoses share some phenotypic traits such as neurological, ophthalmological and cutaneous features. Patients with these diseases are also predisposed to developing multiple endocrine tissue tumors, e.g., pheochromocytomas/paragangliomas are frequent in VHL and NF1. All forms of phakomatosis except CS may be associated with digestive neuroendocrine tumors. More rarely, thyroid cancer and pituitary or parathyroid adenomas have been reported. These susceptibilities are noteworthy, because their occurrence rate, prognosis and management differ slightly from the sporadic forms. The aim of this review is to summarize current knowledge on endocrine glands tumors associated with VHL, NF1, TSC, and CS, especially neuroendocrine tumors and pheochromocytomas/paragangliomas. We particularly detail recent advances concerning prognosis and management, especially parenchyma-sparing surgery and medical targeted therapies such as mTOR, MEK and HIF-2 α inhibitors, which have shown truly encouraging results.